Kungapanegyrisk poesi och paratext hos Petrus Lagerlöf - Sjökvist, Peter (Tidskrift för litteraturvetenskap, 2012)
Royalist Panegyrical Poetry and Paratext in Petrus Lagerlöf The Latin poetry of the Uppsala professor and historiographus regni Petrus Lagerlöf (1648–1699) has attracted limited attention in modern research, although his Latin diction was highly esteemed and much admired in his own day and in the 18th century. A considerable part of his Latin oeuvre was published as paratexts in the publications of students and colleagues. In this article I examine a number of Lagerlöf ’s poems which contain panegyrics superficially praising the king, but in reality address other people. In the poems we come upon ideas, themes and topoi that recur as necessary ingredients in the works of many other authors in the later Caroline period as well. However, in the poems addressing young students it is especially interesting to note the different arguments serving to excuse their young age. In fact, Lagerlöf demonstrates that this excusatio propter infirmitatem can be used as an effective means in royal panegyrics.